2015
DOI: 10.1371/journal.pone.0145482
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Speed Selection and Psycho-Physiological Load during a Mountain Ultramarathon

Abstract: BackgroundExercise intensity during ultramarathons (UM) is expected to be regulated as a result of the development of psycho-physiological strain and in anticipation of perceived difficulties (duration, topography). The aim of this study was to investigate the dynamics of speed, heart rate and perceived exertion during a long trail UM in a mountainous setting.MethodsFifteen participants were recruited from competitors in a 106 km trail mountain UM with a total elevation gain and loss of 5870 m. Speed and gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 34 publications
8
41
5
1
Order By: Relevance
“…In contrast to these findings, we measured in a previous study on trained UM runners a higher magnitude of speed loss in faster compared to slower runners, no significant relationship between the variability of speed and performance level, and a novel significant negative relationship between the total time stopped and performance level, in a long mountain UM (Kerhervé, Millet & Solomon, 2015). Additionally, speed on level, uphill and downhill sections increased in the last 10% of the event.…”
Section: Introductioncontrasting
confidence: 98%
See 4 more Smart Citations
“…In contrast to these findings, we measured in a previous study on trained UM runners a higher magnitude of speed loss in faster compared to slower runners, no significant relationship between the variability of speed and performance level, and a novel significant negative relationship between the total time stopped and performance level, in a long mountain UM (Kerhervé, Millet & Solomon, 2015). Additionally, speed on level, uphill and downhill sections increased in the last 10% of the event.…”
Section: Introductioncontrasting
confidence: 98%
“…A recent study from our group also reported parabolic pacing during a 105 km mountain UM, characterised by a decrease of speed at all gradient categories in the later stages of the event (70–90% of total event duration), and by a final increase in speed in the last 10% of the event (Kerhervé, Millet & Solomon, 2015). The presence of an increase in speed in the last 10% section of the event was discussed as an indicator of conservative pacing strategies in anticipation of upcoming topographic difficulties, and the use of a speed reserve (Millet, 2011) when the last topographic difficulty was passed.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations